Encouraging impact following 2.5 years of reinforced malaria control interventions in a hyperendemic region of the Republic of Guinea. (December 2016) - Tiffany, Amanda; Moundekeno, Faya; Traoré, Alexis; Haile, Melat; Sterk, Esther; Guilavogui, Timothée; Genton, Blaise; Serafini, Micaela; Grais, Rebecca
Abstract Background Malaria is one of the principal causes of morbidity and mortality in the Republic of Guinea, particularly in the highly endemic regions. To assist in malaria control efforts, a multi-component malaria control intervention was implemented in the hyperendemic region of Guéckédou Prefecture. The coverage of the intervention and its impact on malaria parasite prevalence were assessed. Methods Five cross-sectional surveys using cluster-based sampling and stratified by area were conducted from 2011 to 2013 in three sous-préfectures of Guéckédou Préfecture that received the intervention: Guéckédou City, Tékoulo and Guendembou in addition to one comparison sous-préfecture that did not receive the intervention, Koundou. Surveys were repeated every 6 months, corresponding with the dry and rainy seasons. Rapid diagnostic tests (RDT) were used to diagnose malaria infection. In each selected household, bed net use and ownership were assessed. Results A total of 35, 123 individuals participated in the surveys. Malaria parasite prevalence declined in all intervention sous-préfectures from 2011 to 2013 (56.4–45.9 % in Guéckédou City, 64.9–54.1 % in Tékoulo and 69.4–56.9 % in Guendembou) while increasing in the comparison sous-préfecture (64.5–69 %). It was consistently higher in children 5–14 years of age followed by those 1–59 months and ≥15 years. Indicators of intervention coverage, the proportion of households reporting ownership of at least one bed net and the proportion of survey participants with fever who received treatment from a health facility or community health worker also increased significantly in the intervention areas. Conclusions Implementation of the multi-component malaria control intervention significantly reduced the prevalence of malaria in the sous-préfectures of intervention while also increasing the coverage of bed nets. However, malaria prevalence remains unacceptably high and disproportionately affects children <15 years of age. In such situations additional vector control interventions and age specific interventions should be considered.